EFEKTIFITAS SISTEM INTEROPERABILITAS BERBASIS WEB DI RUMAH SAKIT TINGKAT II UDAYANA DENPASAR - Aprillia Ayu Anggraeni; Agus Donny Susanto; Agus Tommy Adi Prawira; Nyoman Ngurah Adisanjaya (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTUdayana Denpasar Hospital is a hospital that organizes RL3 reporting services that have not been computerized. The information reporting system is still manually recaped by officers. The purpose of the research is to know the effectiveness of using web-based interoperability systems to speed up the reporting process conducted by officers in hospitals.The research design uses the Pre Experimental Design method with the design of One Group PreTest – PostTest Design. The method of system development is System Development Life Cycle (SDLC). Programming languages use Perl Hypertext Preprocessor (PHP), Hypertext Markup Language (HTML), Cascading Style Sheets (CSS) and databases used by My Structure Query Language (MySQL).The usability test results on the system meet the usability standard of 73,11% or can be classified